Educational Values in Islam Surah Al-Furqon Verses 63-77 - Arika Ratmi Ningrum; Dzulfikar Akbar Romadlon (Universitas Muhammadiyah Sidoarjo, 2022)
This article aims to explore moral education in the concept of 'Ibadur Rahman through the interpretation of Al-Azhar, so that the understanding of moral education is more varied and more comprehensive. The research approach used is library research whose data is obtained from a literature review with a theoretical and philosophical approach. The results of the study found that the value of moral education contained in Q.S Al-Furqon verses 63-77 Tafsir Al-Azhar by the Hamka of Education is divided into 3: aqidah education, sharia education and moral education.